Economic model for obtaining cyclodextrins from commercial cgtase - Luciana Numata Koga; Vanderson Carvalho Fenelon; Juliana Harumi Miyoshi; Cristiane Moriwaki; Kamila Byanca Baldin Wessel; Camila Sampaio Mangolim; Graciette Matioli (Universidade de São Paulo, 2021)
A repetitive batch process was employed followed by membrane ultrafiltration system to produce low-cost cyclodextrins (CDs) using commercial enzymes Toruzyme® cyclomaltodextrin glucanotransferase (CGTase) and its kinetic parameters were determined. The ultrafiltration system enabled the removalof inhibitory products from the reaction medium, allowing the enzyme to be recovered for reuse. A 10 kDa membrane was used to separate the different CDs produced by the CGTase. The substrates evaluated were maltodextrin, corn starch and cassava starch at 5, 10 and 15% (w/V), in the presence and absence of 10% (V/V) ethanol. After reaction for 132 h, 10% (w/V) cassava starch in the presence of ethanol provided the best results with 32.1 mg/mL of β-CD. Maximum production occurred after 72 h of reaction, with a yield of 87.4% of β-CD and an α-CD, β-CD and γ-CD production ratio of 1:1:0.08 g, respectively. When eight repetitive batches of 72 h followed by ultrafiltration and crystallization of β-CD were performed, 2.1 g of precipitate was obtained with a purity of 67.6% β-CD. The supernatant from the crystallization process was lyophilized and resulted in 35.3% α-CD. The developed model can be used industrially for the production of low cost CDs from easily obtained raw material.